Doença celíaca nas doenças neurológicas da criança e do adolescente [ - Luiz Roberto de Oliveira (2007)
Celiac disease (CD) is a cronic inflammatory enteropathy that occurs ingenetically predisposed individuals and is characterized by reversible small intestine mucosal damage caused by permanent intolerance to dietary gluten. Gluten sensitivity is a state of heightened immunological responsiviness to ingested gluten in genetically susceptible individuals. Occurs in numerous clinical conditions even in the absence of enteropthy. The uniting factor is that withdrawal of gluten mitigates symptoms in a significant number of individuals with these gluten associated diseases. Antigliadin and antiendomysium antibodies aremarkers of untreated CD. The use of these markers in screening has revealed the frequency of CD among symptoms-free individual to be high. Neurological complicatiions are unusual manifestations of CD. A high frequency of antigliadin antibodies was demonstrated in adult patients with neurological dysfunction of unknown cause. Since neurological dysfunction can occur in CD, in this study we investigated if theres association among CD and neurological disorders of unknow cause in children and adolescents and the prevalence of celiac antibodies in thispatients. We estimated the serum antiendomysium and IgA and IgG antigliadin antibodies in 245 neurological patients who were divided in two groups. There were 146 patients with neurological disorders of unknown cause despite complete investigation (group 1) and 99 patients with neurological diagnosis with specific causes (group 2). Positive titres of antibodies were evident in 10 patients (6,8%) from group 1: six had only antigliadin antibodies, two only antiendomysium antibodies and two both antibodies titres. Three (3,0%) patients from group 2 were found to have positive titres of antigliadin antibodies. No patient from this grouphad positive antiendomysium antibodies. Small intestine biopsy in seven out of 10 antibodies positive from group 1 (with no specific diagnosis) revealed histological evidence of CD in one (0,7%), no specific findings in four (2,7%) and no lesion in two (1,4%). No patient from group 2 (specific diagnosis) had histological evidence of CD in intestinal biopsy. Our findings suggest that, different from studies performed in adults, there is no relationship between neurological dysfuntion of unknow cause in pediatric patients and CD, thus screening for this disease does not be routinely included in the diagnostic evaluation of all these children.